RETRACTED: The Influence of Transformational Leadership Style, Organizational Culture and Work Motivation on Employee Performance at PT. Happy Idkho Mandiri - Tsalisa Salma Nasir; Ahmad Cik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This thesis is the result of a quantitative study that aims to analyze the effect of Transformational Leadership Style, Organizational Culture and Work Motivation on Employee Performance at PT. Bahagia Idkho Mandiri. The technique used is to use primary data in the form of questionnaires to 109 employee respondents who work at PT. Bahagia Idkho Mandiri with the Simple Random Sampling method. Based on the results of the Model Feasibility test (F Test), the results of Fcount were 42.905 > Ftable 2.69 with a Sig value of <.001, which is below 0.05. And if seen from the results of the Hypothesis Test (t test) obtained t count (X1) Transformational Leadership Style is 3.288, (X2) Organizational culture is 2.355 and (X3) Work motivation is 5.769 and the Sig value (X1) Transformational Leadership Style is 0.001, (X2) Organizational culture is 0.024 and (X3) Work motivation is <.001 which means all Sig numbers are <0.05. From the results of the evidence above, it can be concluded that the results of the analysis of the Influence of Transformational Leadership Style, Organizational Culture and Work Motivation are proven positive and significant for employee performance at PT. Bahagia Idkho Mandiri.